Therapeutic Interventions for Expressive Language Disorders in Early Childhood: A Qualitative Case Study - M. Fakhry Asa Fazary; Sugiyanta Sugiyanta; Viera Wardhani (Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2025)
This study examines therapeutic interventions for expressive language disorders in early childhood through a qualitative case study approach. Using an indigenous psychology perspective, data were collected through observations, semi-structured interviews, and document analysis over a two-month period at a psychology and therapy institution. The findings indicate that behavior-based therapeutic interventions, when flexibly adapted to children’s developmental characteristics and contextual conditions, effectively support expressive language development. Differences in age and communicative readiness influenced therapeutic strategies and child responsiveness. The study also highlights the importance of parent–therapist collaboration in creating supportive communicative environments, particularly in contexts with limited parent–child verbal interaction. Although limited in scope, this study provides context-sensitive insights into therapeutic practices for expressive language disorders and contributes to a deeper understanding of early language intervention in early childhood education and therapy settings.